lncRNA H19 as a molecular rheostat in autoimmunity: orchestrating miRNA-mediated gene regulation and immune cell reprogramming - Muhammed, Thikra Majid; Mukhlif, Mahmood Yaseen; Hossein, Ahmed; S, Renuka Jyothi; Thakur, Vishal; Mishra, Swati; Chauhan, Ashish Singh; Shuhata, Mahmood Hasen; Alnajar, Mohammed Jawad; Hammoodi, Hayder Abdulhasan (Naunyn-Schmiedeberg's archives of pharmacology, 2025)
The long non-coding RNA H19 (lncRNA H19) functions as a crucial regulator that controls various biological processes especially in immunological responses and autoimmune disease pathogenesis. Autoimmunity develops through complex interactions between genetic factors and environmental triggers and epigenetic changes which result in improper immune reactions against self-antigens. Research findings demonstrate that lncRNA H19 functions as a key regulator which controls immune cell behavior and controls inflammatory pathways and epigenetic regulatory mechanisms. The immune system dysregulation caused by H19 leads to changes in autoimmune disease progression and clinical symptom development. The balance between pro-inflammatory and anti-inflammatory cytokine production is controlled by lncRNA H19 through its interactions with NF-κB signaling cascade and multiple microRNA networks. The immunological tolerance mechanism depends on lncRNA H19 to control T cell differentiation through its regulation of regulatory T cells and T-helper 17-cell populations. The altered expression of lncRNA H19 in autoimmune diseases makes it an attractive subject for research as both a diagnostic biomarker and therapeutic target. This review summarizes recent findings to explain how lncRNA H19 functions in autoimmune disease immunopathogenesis and its therapeutic potential.